Analysis of the Needs of Interactive Multimedia Learning Innovation Containing Pancasila Student Profiles in Elementary Schools - Fathonah, Atiek Sari; Chotimah, Umi; Maharani, Siti Dewi (Papanda Publisher, 2025)
The integration of Pancasila values in basic education plays an essential role in shaping students' character in accordance with the Pancasila Student Profile. However, conventional and less innovative learning approaches have resulted in students being less active and not fully internalizing these character values. This study aims to analyze the need for learning innovation through the development of interactive multimedia that integrates Pancasila Student Profile values at SDN 4 Ngulak, Sanga Desa District, Musi Banyuasin Regency. The research employed a descriptive method, combining both quantitative and qualitative approaches, with 25 students and two teachers as participants. Data were collected using a Likert-scale questionnaire (1–5) and observation sheets, and then analyzed descriptively through percentage calculations and interpretation of the observation results. The findings indicate that the need for interactive multimedia development falls into the very high category, with an overall average score of 87.7%. Specifically, learning needs reached 89%, learning media 87%, learning technology 86%, material interest 85%, interactive multimedia 88%, and expectations for interactive multimedia 90%. These results show that teachers and students have strong enthusiasm for using interactive multimedia as an engaging, practical, and effective learning tool. Both groups believe that engaging, contextual, and user-friendly media are essential to support the internalization of the six dimensions of the Pancasila Student Profile: faith and devotion to God Almighty, global diversity, cooperation, independence, critical thinking, and creativity. In conclusion, interactive multimedia development is essential to make learning more engaging, contextual, and character-oriented in line with the Independent Curriculum.